Surga dalam Mimesis: Representasi Surga dalam Cerpen ‘Sang Pendeta dan Kekasihnya’ Karya Yukio Mishima - Akun Akun (Humaniora, 2010)
Mimesis is the representation of reality. This writing focuses on the analysis of three different representations of heaven in a short story The Preacher and His Lover by Yukio Mishima. The first representation is from the narrator’s interpretation, stressing on the existence of an ideal heaven in common people’s point of view, employing this worldly measurement in describing the ideal heaven. The second representation comes from Great Preacher with his view that the represented heaven is a place where he can enjoy the earthly and bodily enjoyment that he avoids in this world. And lastly, the representation from the Great Concubine who puts forward a contradictory (especially with the Great Preacher) point of view that the dreamed heaven is not at all the enjoyment that people experience in this world.